2014
DOI: 10.1111/pce.12274
|View full text |Cite
|
Sign up to set email alerts
|

A step towards understanding plant responses to multiple environmental stresses: a genome‐wide study

Abstract: In natural habitats, especially in arid areas, plants are often simultaneously exposed to multiple abiotic stresses, such as salt, osmotic and heat stresses. However, most analyses of gene expression in stress responses examine individual stresses. In this report, we compare gene expression in individual and combined stresses. We show that combined stress treatments with salt, mannitol and heat induce a unique pattern of gene expression that is not a simple merge of the individual stress responses. Under multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 54 publications
4
78
0
Order By: Relevance
“…combination unique DEGs). The extent and composition of combination unique DEGs varied among different studies, but it has been shown that the multifactorial nature of stress combinations limits the ability to predict plants' transcriptional responses based on the corresponding single stresses (Prasch and Sonnewald, 2013;Rasmussen et al, 2013;Sewelam et al, 2014;Suzuki et al, 2016). Investigation of the transcriptional changes of 1,550 common stress DEGs yielded four different response patterns of triple-and double-stress combinations that varied in response mode partitions (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…combination unique DEGs). The extent and composition of combination unique DEGs varied among different studies, but it has been shown that the multifactorial nature of stress combinations limits the ability to predict plants' transcriptional responses based on the corresponding single stresses (Prasch and Sonnewald, 2013;Rasmussen et al, 2013;Sewelam et al, 2014;Suzuki et al, 2016). Investigation of the transcriptional changes of 1,550 common stress DEGs yielded four different response patterns of triple-and double-stress combinations that varied in response mode partitions (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In their natural habitats, plants are exposed to multiple stresses, and responses to them in general differ from the responses to single stresses or a sum of the individual stresses. Transcriptomics and proteomics studies were the first to reveal the complexity of the response to multiple stresses (Rizhsky et al, 2002;Koussevitzky et al, 2008;Rasmussen et al, 2013;Rivero et al, 2014;Sewelam et al, 2014). Besides the transcriptional responses to multiple stresses, their physiological consequences have been studied only recently.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that certain stress combinations cancel each other out, whereas combinations of others can be devastating for plant performance and yield. However, this cannot be predicted from knowledge of the single stresses alone: gene expression studies indicate that combining the stresses due to salt, mannitol, and heat treatments induces unique gene expression patterns that cannot be simply inferred from those induced by the individual stresses (Sewelam et al, 2014). Another study compared transcriptome changes in 10 Arabidopsis ecotypes in response to cold, heat, high light, salt, and flagellin treatments, as well as combinations of these stresses.…”
Section: Future Perspectivesmentioning
confidence: 99%